Coercion and compulsion in mental healthcare-An international perspective - Molodynski, A; Turnpenny, L; Rugkåsa, J; Burns, T; Moussaoui, D; Burns, J; Dawson, J; Kallert, T; Okasha, A; Rose, D; Sharma, S; Swanson, J; et al. (Elsevier, 2014)
Background: Coercion has always existed in psychiatry and is increasingly debated. The 'move into the community' in many countries over recent decades and the evolution of community services have substantially altered the locus of coercion. In many countries psychiatric services remain poorly funded and patchy. Substantial differences between regions and countries in the provision of services, the role of the family, and the wider economic and political climate are likely to lead to different sources and experiences of coercion. Discussion: This paper explores a number of factors that may affect the prevalence and type of coercion in psychiatric services and in society and their impact upon those with severe mental illnesses. Differences in service provision are explored and wider societal issues that may impact are considered along with relevant evidence. Conclusions: Coercion is commonly experienced by those with severe mental illnesses but is poorly understood. The vast majority of research relates to High Income Group countries with developed community services and formal mental health legislation that adopt the so-called 'medical model'. Further research and collaboration is urgently required to increase our understanding of these issues, which are difficult to define and measure. An evidence base that is relevant worldwide, not just to a small group of countries, is needed to inform training and the care of all patients. A particular focus must be expanding our knowledge and understanding of coercion in cultures outside those where such research has traditionally taken place to date. © 2013 Elsevier B.V.